2022
DOI: 10.4018/978-1-6684-5741-2.ch014
|View full text |Cite
|
Sign up to set email alerts
|

To Identify the Accessibility and Performance of Smart Healthcare Systems in IoT-Based Environments

Abstract: Internet of things (IoT) is a prominent terminology that has gaining enormous assistance over past years among researchers and professionals. In general, IoT is a combination of interdependent computing devices such as sensors, actuators, microprocessors and other sink nodes that are able to transfer data over network without compelling human-to-human or human-to-machine communication. Besides, by reason of its interdisciplinary approach, IoT has been substantial in evolving distinct aspects of conventional e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The Internet of Things (IoT), on the other hand, is a system of linked computing devices, including microprocessors, sensors, actuators, and other nodes, that may exchange data in real time without the need for direct human-to-human or human-to-machine communication. The Internet of Things (IoT) has significantly improved several conventional e-healthcare techniques because of its interdisciplinary character [34].Every person, particularly those who are ill, needs comfortable indoor air since each person's breathing intensity varies depending on their activity. The continuous active ventilation systems in indoor is the only effective means of supplying comfortable air with thermal comfort [35].…”
Section: Fig3 Outcome Of Co Absorption For Human 4 Chemistry-related ...mentioning
confidence: 99%
“…The Internet of Things (IoT), on the other hand, is a system of linked computing devices, including microprocessors, sensors, actuators, and other nodes, that may exchange data in real time without the need for direct human-to-human or human-to-machine communication. The Internet of Things (IoT) has significantly improved several conventional e-healthcare techniques because of its interdisciplinary character [34].Every person, particularly those who are ill, needs comfortable indoor air since each person's breathing intensity varies depending on their activity. The continuous active ventilation systems in indoor is the only effective means of supplying comfortable air with thermal comfort [35].…”
Section: Fig3 Outcome Of Co Absorption For Human 4 Chemistry-related ...mentioning
confidence: 99%
“…Pavitra et al [17] suggested a concept of IoT-based environments to determine the performance and accessibility of smart healthcare systems. On the other side, traditional healthcare systems no longer fulfill the demands of a frequently expanding and developing community.…”
Section: Related Workmentioning
confidence: 99%